1997
DOI: 10.1086/647686
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Contamination Due to Methicillin-Resistant Staphylococcus aureus: Possible Infection Control Implications

Abstract: We concluded that inanimate surfaces near affected patients commonly become contaminated with MRSA and that the frequency of contamination is affected by the body site at which patients are colonized or infected. That personnel may contaminate their gloves (or possibly their hands) by touching such surfaces suggests that contaminated environmental surfaces may serve as a reservoir of MRSA in hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
412
5
11

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(436 citation statements)
references
References 0 publications
8
412
5
11
Order By: Relevance
“…It has already been reported that HCWs' hands may become contaminated after contact with inanimate surfaces, 30 " 32 and the environment has been suggested as a possible reservoir for nosocomial pathogens in the hospital setting. 32 None of these studies, including the current one, were designed to evaluate whether such contamination could result in pathogen transmission to susceptible patients. However, contact with a contaminated environment may play a role in high-risk newborn nurseries or neonatal intensive care units, particularly regarding bacteria that can survive for prolonged periods in inanimate environments.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been reported that HCWs' hands may become contaminated after contact with inanimate surfaces, 30 " 32 and the environment has been suggested as a possible reservoir for nosocomial pathogens in the hospital setting. 32 None of these studies, including the current one, were designed to evaluate whether such contamination could result in pathogen transmission to susceptible patients. However, contact with a contaminated environment may play a role in high-risk newborn nurseries or neonatal intensive care units, particularly regarding bacteria that can survive for prolonged periods in inanimate environments.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Previous studies have demonstrated MRSA contamination on a variety of environmental surfaces in the hospital setting. 6,7 The dental operatory may also be contaminated with MRSA and become a potential source of MRSA.…”
Section: Introductionmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) has emerged as a significant nosocomial infectious threat, prompting several studies that have identified MRSA reservoirs in the hospital setting including bed rails, countertops, floors, bed linens, tables and blood pressure cuffs (Boyce et al, 1997;Blythe et al, 1998). Because of frequent dermal contact by numerous users, one reservoir of interest is computer keyboards, which have been shown to harbor MRSA in the hospital setting (Bures et al, 2000;Devine et al, 2001;Neely et al, 2005;Wilson et al, 2006).…”
mentioning
confidence: 99%